2011
DOI: 10.1073/pnas.1115249108
|View full text |Cite
|
Sign up to set email alerts
|

Control of skin cancer by the circadian rhythm

Abstract: Skin cancer is the most common form of cancer in the United States. The main cause of this cancer is DNA damage induced by the UV component of sunlight. In humans and mice, UV damage is removed by the nucleotide excision repair system. Here, we report that a rate-limiting subunit of excision repair, the xeroderma pigmentosum group A (XPA) protein, and the excision repair rate exhibit daily rhythmicity in mouse skin, with a minimum in the morning and a maximum in the afternoon/evening. In parallel with the rhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
268
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 205 publications
(286 citation statements)
references
References 37 publications
15
268
3
Order By: Relevance
“…Consistently, we show that oxidative phosphorylation is one of the most significant categories among genes up-regulated in the skin of Bmal1 −/− mice at ZT22 (4:00 AM). The regulation of circadian epidermal proliferation likely involves canonical clock mechanisms rather than clock-independent function of BMAL1, because circadian S-phase also is obliterated in Cry1 −/− ;Cry2 −/− mice (13). In contrast to our findings, another study reported reduced proliferation in Bmal1 −/− epidermis (12).…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Consistently, we show that oxidative phosphorylation is one of the most significant categories among genes up-regulated in the skin of Bmal1 −/− mice at ZT22 (4:00 AM). The regulation of circadian epidermal proliferation likely involves canonical clock mechanisms rather than clock-independent function of BMAL1, because circadian S-phase also is obliterated in Cry1 −/− ;Cry2 −/− mice (13). In contrast to our findings, another study reported reduced proliferation in Bmal1 −/− epidermis (12).…”
Section: Discussioncontrasting
confidence: 55%
“…The mammalian epidermis is now emerging as a prime model to study the role of the circadian clock in cell proliferation and cancer susceptibility (8,12,13). Previous studies have established circadian variation in proliferation in several tissues, including mouse epidermis (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations